Is Wear Still a Concern in Total Knee Arthroplasty With Contemporary Conventional and Highly Crosslinked Polyethylene Tibial Inserts in the mid- to Long-Term? - Devin P. Asher, BS; Jennifer L. Wright, MS; Deborah J. Hall, BS; Hannah J. Lundberg, PhD; Douglas W. Van Citters, PhD; Joshua J. Jacobs, MD; Brett R. Levine, MD, MS; Robin Pourzal, PhD (Arthroplasty Today)
Background: Modern literature has brought into question if wear of tibial inserts made from conventional or highly crosslinked polyethylene (HXL PE) is still a factor limiting longevity of total knee arthroplasty (TKA) in the mid- to long-term. It is the objective of this study to determine: 1) most common causes of mid- to long-term TKA failure, 2) the prevalence of delamination, and 3) the medial/lateral linear wear rates of conventional and HXL PE tibial inserts retrieved in the mid- to long-term. Methods: A tibial insert retrieval cohort of 107 inserts (79 conventional, 28 HXL PE) with a minimum time in situ of 6.5 years (mean 11.7 ± 4) was studied. Failure causes were determined from chart-review, delamination presence was assessed microscopically, and medial/lateral linear wear was determined by minimal thickness changes measured with a dial-indicator. Results: The most common mid-to long-term etiologies for failure were instability (44.9%), PE wear 15%), aseptic loosening (14%), and infection (13.1%). Delamination occurred in 70% of inserts (72.1% conventional, 64.3% HXLPE). Gross material loss due to delamination appeared to be the underlying reason for at least 33.3% of cases exhibiting instability. Of the cases removed for infection, 75% exhibited no histopathological hallmarks of acute infection. The medial/lateral wear rates were 0.054/0.051 (conventional) and 0.014/0.011 (HXL) mm/y, respectively. Conclusions: Polyethylene wear still appears to be a major primary and secondary cause for TKA revision in the mid- to long-term. Wear may manifest as destabilizing delamination or as continuous release of fine wear particles potentially resulting in inflammatory responses and subsequent failure.